PENGEMBANGAN MEDIA VIDEO TUTORIAL PADA MATERI DESAIN UI/UX INTERFACE UNTUK MENINGKATKAN KEMAMPUAN MENCIPTA DI MATA PELAJARAN DESAIN BRIEF KELAS XI DKV SMKN 1 JOMBANG: Indonesia - Agung Setiawan, Shandi; Fitri Kholidya, Citra (Jurnal Mahasiswa Teknologi Pendidikan, 2026)
Abstract This study aims to develop instructional media in the form of a video tutorial on UI/UX interface design materials and to examine its feasibility and effectiveness in improving the creative abilities of eleventh-grade students of Visual Communication Design (DKV) at SMKN 1 Jombang. The background of this study is based on students’ low ability to understand and apply UI/UX concepts, particularly in digital prototyping, as well as the limited availability of visual and practical learning media. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects were 35 eleventh-grade DKV students at SMKN 1 Jombang. Data collection instruments included validation sheets from material experts, instructional design experts, and media experts, student response questionnaires, and a rubric for assessing creative ability through UI/UX design project tasks. The results showed that the developed video tutorial was considered very feasible based on evaluations by media experts, material experts, and instructional design experts. Student responses to the use of the video tutorial were also categorized as very good. Furthermore, posttest results indicated that the average student score exceeded the Minimum Mastery Criteria (KKM) and classical learning mastery was achieved. Therefore, the video tutorial media was declared effective in improving students’ creative abilities. Thus, the Figma-based UI/UX video tutorial can be used as an effective instructional medium to support UI/UX design learning in vocational high schools. Keywords: Video tutorial, UI/UX interface, creative ability, Figma, vocational high school (Visual Communication Design)